ECONOMIC BURDEN OF TYPE 2 DIABETES IN MYANMAR - Oo, Wah Khaing; Ko, Ko; Riewpaiboon, Arthorn; Youngkong, Sitaporn (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION The burden of diabetes, especially type 2 diabetes, is a growing public health concern in Myanmar. However, no study explored the economic consequences of the disease. Therefore, this study aimed to estimate the economic burden of type 2 diabetes from a societal perspective. METHODOLOGY This study was a retrospective, prevalence-based cost of illness analysis. Data were collected from 94 randomly selected patients with type 2 diabetes who received treatment at the Diabetes and Endocrinology department of North Okkalapa teaching hospital in Yangon, Myanmar during 2017-2018. A micro-costing approach was applied in the cost calculation. One-way sensitivity analysis was performed to check the uncertainty of the results. RESULTS The estimated total cost of type 2 diabetes was 104,386 USD (1 USD = 1520 kyat) for the 2019 fiscal year. Of which, 66% was direct medical cost, 18% was direct non-medical cost, and 16% was indirect cost. The cost per patient per year was 1110 USD, 88% of per capita gross domestic product of Myanmar. It indicates that type 2 diabetes has a substantial impact on the country’s growing economy, and this will be greater with increasing prevalence in the coming year. Furthermore, the cost of informal care contributed to 48% of the direct non-medical cost. So, the results indicate that the disease affected not only the individual but also the caregivers, including family, relatives, and friends. CONCLUSION The results of this study highlighted that an appropriate strategy with cooperative effort is urgently necessary to decrease prevalence of disease and its associated complications.